PENDIDIKAN BERBASIS LITERASI AL-QUR’AN: ANALISIS TERHADAP AYAT-AYAT IQRA’ DAN RELEVANSINYA DALAM PENGUATAN BUDAYA AKADEMIK - Yahya Zahid Ismail; Afrizal El Adzim Syahputra; Ika Setiawati (Prodi PAI Fakultas Tarbiyah IAI Sunan Giri Trenggalek, 2025)
This study aims to analyze the concept of education based on Qur’anic literacy through an examination of the Iqra’ verses and their relevance in strengthening academic culture in the contemporary era. The Iqra’ verses in Surah Al-‘Alaq (1–5) are understood not merely as a command to read in a textual sense, but also as an epistemological foundation for the development of knowledge that integrates revelation and reason. This research employs a qualitative method with a thematic (maudhu’i) tafsir approach, examining various interpretations from classical and contemporary scholars to uncover the substantive meaning of literacy within the Qur’an. The findings indicate that literacy from a Qur’anic perspective encompasses activities such as reading, understanding, researching, and developing knowledge in a critical and reflective manner. These values are aligned with the principles of academic culture, including academic integrity, openness of thought, and the pursuit of truth. Furthermore, the concept of Iqra’ emphasizes the importance of the spiritual dimension in intellectual activity, thereby fostering a balance between intellectual and moral intelligence. Thus, education based on Qur’anic literacy holds significant relevance in building an academic culture that is not only oriented toward the mastery of knowledge but also toward character formation and integrity. This study recommends the integration of Qur’anic literacy values into the Islamic education curriculum as a strategic effort to enhance the quality of holistic and sustainable education.